POTENSI PENGEMBANGAN TERNAK KERBAU DENGAN POLA PEMELIHARAAN CROP UVESTOCK SYSTEM DI PROPINSI RIAU - Yayu Zurriyati dan; Dwi Sisri Yenni (Jurnal Peternakan, 2007)
Buffalo (Bubalus hubaUs) is the one potential supplier for red meat. But, it contribution was lower than the cattle meat. The most population of buffa10 in Riau Province is at Kampar Regency. Generally, people at Kampar Regency COll8ume the buffalo milk, as IIdadih", that ingredient nutrient for the body healthy. Up to now, the buffalo productivity is lower, because of the extensive breeding management. Forward, the technology support in management of buffalo breeding was needed. The buffalo pattern integrated with food crop and estate plantation is alternative introduction to increase the buffalo productivity.falo (Bubalus hubaUs) is the one potential supplier for red meat. But, it contribution was lower than the cattle meat. The most population of buffa10 in Riau Province is at Kampar Regency. Generally, people at Kampar Regency COll8ume the buffalo milk, as IIdadih", that ingredient nutrient for the body healthy. Up to now, the buffalo productivity is lower, because of the extensive breeding management. Forward, the technology support in management of buffalo breeding was needed. The buffalo pattern integrated with food crop and estate plantation is alternative introduction to increase the buffalo productivity.